Case report: GLP1RA for the treatment of diabetes in liver transplanted people. Do they increase the risk of pancreatitis? - Grancini, Valeria; Cogliati, Irene; Gaglio, Alessia; Resi, Veronica; Orsi, Emanuela (Frontiers in Endocrinology, 2024)
The incidence of acute pancreatitis (AP) in liver transplanted people is reported to be 1.5-8%. On the other hand, the evidence for a causal relationship between glucagon-like peptide 1 receptor agonists (GLP1RAs) and pancreatitis in people with type 2 diabetes is still weak. In addition, there are currently no data on a possible increased risk of AP in liver-transplanted individuals with diabetes treated with GLP1RAs. In a population of liver-transplanted individuals with diabetes receiving GLP1RA-based therapy, we reported an incidence of AP of 3.0% (two subjects). No cases were reported in liver-transplanted individuals with diabetes receiving SGLT2 inhibitors, insulin or metformin, neither in kidney or lung-transplanted patients treated with GLP1RAs. In both patients with AP, the only additional risk factor for its development was a history of re-transplantation (liver or combined kidney/liver). For this reason, we suggest particular caution when considering GLP1RAs-based therapies in liver transplanted patients with multiple risk factors for AP, such as a history of repeated and complex abdominal surgery.